Applying Fibrin Glue under Pleurography for Intractable Secondary Spontaneous Pneumothorax - Cho, Jeong Su; Ahn, Hyo Yeong; Kim, Yeong Dae; I., Hoseok; Eom, Jung Seop (The Thoracic and Cardiovascular Surgeon, 2019)
Background Prolonged air leakage is a problem that can frequently develop in patients with a secondary spontaneous pneumothorax (SSP) or in those who undergo thoracic surgery. However, the management of an air leak is difficult and reoperation might be avoided due to several reasons including adhesions. Herein, we introduce a fibrin glue application under pleurography (FGAP) and short-term outcomes in patients who underwent this procedure.Methods FGAP was performed in 20 patients with an intractable persistent air leakage who had poor lung function, comorbidities to undergo general anesthesia and were expected severe adhesions due to previous surgery. All medical records were retrospectively reviewed.Results Eighteen cases sealed soon after dropping the glue. One patient had a prolonged air leak for 12 days and another patient required an operation to control air leakage 16 days after the procedure. The mean duration of postoperative drainage was 4.17 ± 2.11 days (range: 3–14 days). No postprocedural complications were recorded. The mean duration of follow-up was 12.01 ± 5.02 months (range: 4–22 months).Conclusion FGAP could be a treatment option to seal air leaks, especially in cases with intractable air leakage.
Keywords: fibrin glue; pleurography; pneumothorax